2008
DOI: 10.1007/s00217-008-0951-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drying temperature on polyphenolic content and antioxidant activity of apricots

Abstract: This study was carried out in order to check for the influence of drying parameters on the phenolic compounds and antioxidant activity on two apricot cultivars (Pelese and Cafona) using two sets of air drying temperatures: (1) air temperature at 55°C; (2) air temperature at 75°C. Whole fresh and dried fruits were assessed for: phenolics, ascorbic acid, antioxidant activity and redox potential (all parameters were calculated on a dry matter basis). Analysis of data shows that the decrease in chlorogenic and neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
124
4
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(168 citation statements)
references
References 41 publications
34
124
4
6
Order By: Relevance
“…The observed gap was just 0.0033 g GAE/l (9.966 mg GAE/g), meaning 6.6%. Madrau et al (2009) o C a large variety of mushrooms, extracted them in aqueous ethanol, and the highest extract of total phenols was 15.8 mg GAE/g. Herein, the least extraction was 0.1083 g GAE/l (327.066 mg GAE/g) in DW+Meth.…”
Section: Total Phenolsmentioning
confidence: 99%
See 3 more Smart Citations
“…The observed gap was just 0.0033 g GAE/l (9.966 mg GAE/g), meaning 6.6%. Madrau et al (2009) o C a large variety of mushrooms, extracted them in aqueous ethanol, and the highest extract of total phenols was 15.8 mg GAE/g. Herein, the least extraction was 0.1083 g GAE/l (327.066 mg GAE/g) in DW+Meth.…”
Section: Total Phenolsmentioning
confidence: 99%
“…At high temperature, following Madrau et al (2009) remarks, the PPO enzymatic reaction doesn't occur because of a relative short exposure time. In addition, Lohani and Muthukumarappan (2015) indicated that the phenolic compounds can be liberated by heat treatment, and moreover, Jeong et al (2004) came to the conclusion that phenols should have different bound status along with plant species.…”
Section: Total Phenolsmentioning
confidence: 99%
See 2 more Smart Citations
“…), were retained 64 and 62.5%, respectively, after sun-drying (Table 1). During the drying process, enzyme activity remains high for long periods of time when temperature is maintained among 55-60°C, whereas many enzymes are inactivated after short periods of exposure to temperatures of 75-80°C (MADRAU et al, 2009). Caffeic acid is susceptible to decarboxylation reactions, which can be promoted by either thermal conditions or enzymatic action through decarboxylases to generate vinylphenols (RIZZI & BOEKLEY, 1992).…”
Section: Phenolic Compounds Sun-dryingmentioning
confidence: 99%